Adoption of cloud computing to enhance the healthcare services in Malaysia - Ratnam, K.A. (Institute of Electrical and Electronics Engineers Inc., 2014)
The global healthcare industry is continuing to grow, and it is important to realize that healthcare providers will have to continue to invest in IT based systems to improve overall operations and cross system communications. The study focuses on the relationships between healthcare providers, IT resources and health insurance providers in determining the adoption of cloud computing. The results obtained as result of this study shows that IT resources significantly influences healthcare providers and health insurance providers. The efficiency and clinical services can be improvised with the adoption of the cloud. The findings of this study are presented with reliability analysis, descriptive, factor loading, regression and correlations for IT capability in healthcare services, structural equation modelling is used to determining the overall model fit. Structural equation modelling (SEM) using AMOS 20.0 is used for model fit testing and SPSS 20.0 is used for analysing the descriptive statistics, hypothesis and assumptions for SEM. Â© 2014 IEEE.